2020
DOI: 10.1080/14737167.2020.1779061
|View full text |Cite
|
Sign up to set email alerts
|

The transferability of health technology assessment: the European perspective with focus on central and Eastern European countries

Abstract: Introduction: Lower income European countries have a worse health status and less funds for health care compared to Western Europe. Despite their limited human and financial capacities for conducting Health Technology Assessment (HTA), the need for evidence-based decision-making is growing. Two main approaches emerged as potential solutions: joint clinical assessments on the European level, and simplified procedures relying on the judgements of well-established HTA agencies of Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Methodologically, aHTA may leverage or adapt available international data, economic evaluations, models and/or decisions from the published literature or established HTA agencies to expedite policy decisions while adequately accounting for concerns of transferability and uncertainty. 9 The aHTA process should be pragmatic, though still informed by key HTA principles such as transparency, independence, consultation and contestability.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Methodologically, aHTA may leverage or adapt available international data, economic evaluations, models and/or decisions from the published literature or established HTA agencies to expedite policy decisions while adequately accounting for concerns of transferability and uncertainty. 9 The aHTA process should be pragmatic, though still informed by key HTA principles such as transparency, independence, consultation and contestability.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…18 19 Notably, these are analyses which have been carried out as one part of the HTA process, though the extent to which they have influenced policy or been implemented may be varied or absent (eg, Romania). 9…”
Section: Adaptation Of International Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outdated and non-evidence-based eligibility criteria for novel therapies can prevent PwD receiving new, efficacious technologies, particularly if funding is instead diverted to medications at high prices with limited health gains [73][74][75][76]. It has been suggested that HTA implementation in the Central and Eastern European region be particularly resource-conscious, with transferability of evidence (e.g., clinical evidence, HTA methodology, and policy) between countries in the region emphasized wherever possible [77]. However, the aspects of HTA that are transferable between countries should be carefully considered, given that each country faces its own unique challenges and comprises different populations.…”
Section: Access and Fundingmentioning
confidence: 99%
“…Patients' data come from insurance companies. There is no published article with such complex data on access to OMPs for Slovak patients to date; most of the articles refer rather to the process of drug reimbursement (Kawalec et al, 2017;Malinowski et al, 2019;Tesar et al, 2019;Németh et al, 2020) or access to a limited number of OMPs (Blankart et al, 2011;Tesar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%